High-efficiency nano/micro-reactors for protein analysis. Issue 2 (2nd December 2014) - Li, Yixin; Yan, Ling; Liu, Yun; Qian, Kun; Liu, Bin; Yang, Pengyuan; Liu, Baohong
Abstract : This article reviews the recent advances regarding the development of nanomaterial-based nanoreactors and microfluidic droplet reactors and their applications in protein analysis. Abstract : Protein analysis is always one of the key fields researchers focus on. Recent years has witnessed the rapid development of novel nanomaterials and microfluidic droplets as ideal reactors for protein analysis. This article reviews the recent advances regarding the development of nanomaterial-based nanoreactors and microfluidic droplet reactors and their applications in protein analysis, especially in proteomics. The categories, features and applications of various recently developed micro/nano-reactors have been summarized and future directions and challenges in this field have also been discussed.